Effects of Long-Term Fertilization Management Practices on Soil Microbial Carbon and Microbial Biomass in Paddy Soil at Various Stages of Rice Growth - Xu,Yilan (2018)
ABSTRACT Soil microbial biomass plays a significant role in soils, and it is often used as an early indicator of change in soil quality. Soil microbial biomass is affected by different fertilization management practices. Therefore, the impact of different long-term fertilization management practices on the soil organic carbon (SOC) content, soil microbial biomass carbon (SMBC), and soil microbial biomass nitrogen (SMBN), as well as the soil microbial quotient (SMQ) in the tilled layer (0.00-0.20 m) were studied in the present paper, together with grain yield, in a double-cropping rice (Oryza sativa L.) system. The experiment in NingXiang county of Hunan Province, China, begin in 1986, and the experiment included five fertilization treatments: without fertilizer input (CK), mineral fertilizer alone (MF), rice straw residues and mineral fertilizer (RF), 30 % organic matter and 70% mineral fertilizer (LOM), and 60% organic matter and 40 % mineral fertilizer (HOM). The results showed that there is no significant difference in effect on SOC, SMBC, and SMBN contents and on the SMQ in the paddy field with MF treatment compared with the CK treatment at the main growth stages of early and late rice. The SOC, SMBC, SMBN contents, and the SMQ in the paddy field were highest in the LOM and HOM treatments, followed by the RF treatment, at the main growth stages of early and late rice. The results indicated that grain yields of early and late rice with the LOM, HOM, and RF treatments were higher than the yields under the MF and CK treatments. As a result, combined application of organic matter or rice straw residues with mineral fertilizer is a practice available for increasing SOC and microbial biomass contents in double-cropping rice paddy soils.